Diez grandes poetas vivos de América Latina - Greiff, León de (autor) ((Mini/Extemporáneos ;)
Incluye poesía de León Greiff, Jorge Luis Borges, Jorge Carrera Andrade, Nicolás Guillén, Pablo Neruda, Manuel del Cabral, Juan Cunha, José Lezama Lima, Nicanor Parra y Octavio Paz.